PENERAPAN TEKNIK SELF TALK UNTUK MENINGKATKAN PERCAYA DIRI SISWA KELAS IX-2 DI SMPN 4 BANDA ACEH - Aqilah, Tiqah; Sulistiana, Sulistiana; Aini, Nurul; Bakar, Abu (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to explore the application of self-talk techniques to enhance self-confidence among IX-2 students at SMPN 4 Banda Aceh. The research employs a qualitative method, utilizing data collection through interviews, observations, and document analysis. Participants in this study include students, teachers, and school counselors. The findings indicate that the implementation of self-talk techniques, such as positive affirmations, reframing negative thoughts, visualization, and journaling, significantly impacts the enhancement of students’ self-confidence. Students who practiced these techniques reported increased motivation, improved ability to face challenges, and more active participation in learning activities. Additionally, teachers and counselors noted positive changes in students’ attitudes and behaviors, reflecting heightened self-confidence and social skills. This study concludes that self-talk techniques can serve as an effective strategy to support the development of students’ self-confidence. It is recommended to integrate self-talk practices into educational programs to enable students to fully utilize these techniques for improving academic performance and personal well-being. Penelitian ini bertujuan untuk mengeksplorpenerapan teknik self-talk dalam meningkatkan rasa percaya diri siswa kelas IX-2 di SMPN 4 Banda Aceh. Metode yang digunakan dalam penelitian ini adalah kualitatif, dengan pengumpulan data melalui wawancara, observasi, dan studi dokumentasi. Partisipan dalam penelitian ini terdiri dari siswa, guru, dan konselor sekolah.Hasil penelitian menunjukkan bahwa penerapan teknik self-talk, seperti afirmasi positif, pengubahan pikiran negatif, visualisasi, dan jurnal, memberikan dampak signifikan terhadap peningkatan rasa percaya diri siswa. Siswa yang menerapkan teknik ini melaporkan peningkatan motivasi, kemampuan untuk menghadapi tantangan, serta partisipasi yang lebih aktif dalam kegiatan belajar mengajar. Selain itu, guru dan konselor mencatat adanya perubahan positif dalam sikap dan perilaku siswa, yang menunjukkan peningkatan kepercayaan diri dan kemampuan bersosialisasi. Penelitian ini menyimpulkan bahwa teknik self-talk dapat dijadikan strategi efektif dalam mendukung pengembangan rasa percaya diri siswa. Disarankan untuk mengintegrasikan praktik self-talk dalam program pembelajaran di sekolah agar siswa dapat memanfaatkan teknik ini secara maksimal untuk meningkatkan kinerja akademis dan kesejahteraan pribadi.